Social security cases in Europe: the European Court of Human Rights - Kapuy, Klaus; Pieters, Danny; Zaglmayer, Bernhard (Antwerpen, 2007)
"What aspects of social security are covered by the European Convention on Human Rights? What obligations does a State have in the field of social security to safeguard the rights guaranteed in the Convention? To what extent can a national right to a social security benefit constitute a civil right or even a property right as protected by the Convention? This casebook addresses these questions. It is composed of two main parts. The first gives an overview of the complaints in the field of social security which were brought forward to the European Commission of Human Rights or the European Court of Human Rights. These cases are clustered into six themes: reduction, loss or refusal of benefits; duty to pay social security contributions; equality; illegal migrants; medical treatment; and fair trial. In the second part the reader finds the relevant extracts of the reports, decisions and judgments of more than 90 selected cases before the Strasbourg organs. This book highlights the role of the European Convention on Human Rights in social security matters. It is useful both for further research and education. Moreover, law students as well as legal practitioners will benefit from this case collection as a reference book."